Application of Project Based Learning in Teaching Foreign Languages - Begizova Madina (International Journal on Integrated Education, 2021)
the article describes issues on application and organization of project-based learning in teaching foreign languages. As its known that, projects involve the activation of students: they must make presentations, videos, use the Internet, talk with other people, look for photographs and drawings. As well as, students with different levels of language training can participate in the design work in accordance with their capabilities. For instance, a student who does not speak in English well enough can perfectly draw or skillfully use Internet resources. In this article the author deals with the researches of scientists based on this topic and defines the stages of project designing and its evaluation process.